Effect of Squill Oxymel on Knee Osteoarthritis: A Triple-Blind, Randomized, Controlled Clinical Trial - Mojtaba Taheri; Seyed Mohammad Riahi; Mohammad Kazem Emami meybodi; Mohammad Mahdi Ahmadian-Attari; Somayeh Esmaeili; Roshanak Mokaberinejad (Tehran University of Medical Sciences, 2023)
Osteoarthritis (OA) of the knee is a major health problem in the society. Iranian Traditional Medicine (ITM) or Persian Medicine (PM) as a branch of complementary medicine has been practiced in Iran for many centuries. An herbal medication known as squill oxymel has been used by PM physicians for OA. Our aim is to investigate the effect of squill oxymel on OA of the knee joint. Eighty eight patients were assigned to receive a placebo or squill oxymel syrup (10 ml each morning on empty stomach) for 8 consecutive weeks. Acetaminophen tablets were considered as the rescue medicine. Ultimately, 43 patients in the placebo group and 40 patients in the treatment group completed the trial and were included in the statistical analysis. Patients were followed for 4 weeks after cessation of treatment. The Knee injury and Osteoarthritis Outcome Score (KOOS) questionnaire and Visual Analog Scale (VAS) were considered as the main outcome measures. Laboratory tests including AST, ALT, BUN, Cr plus inflammatory tests including WBC, ESR, and CRP with specific tests i.e. IL6 and SOD at the beginning and the end of intervention were measured. The results showed the positive effect of treatment on the outcome of knee pain (p=0.04) and daily activity (p=0.01) of KOOS after Cessation of treatment. On the other hand, VAS decreased in both treatment and placebo groups while it showed significance intra-group and showed no significance between the two groups. After 4 weeks of cessation of treatment, the positive effect of the squill oxymel on the treatment group continued in some of the subscales of KOOS, including symptoms, knee pain and daily activities, but stopped in the placebo group. In general, both clinically and statistically significant improvement was observed after cessation of treatment. Squill oxymel syrup showed promising results in management of knee OA but future researches with larger sample size and longer duration are necessary.